American structural power within International Financial Governance: from Bretton Woods to globalization - Alencar, Fernando Barcellos de Andrade (Faculdade de Filosofia e Ciências, 2018)
From the 1950s to the 1990s, the international monetary and financial system underwent deep changes with profound consequences, including the breakdown of Bretton Woods and the emergence of the globalized financial system. This paper aims to understand how American domestic political and economic challenges and responses in the 1970s reframed the superpowers’ foreign policy goals with respect to global financial governance. Drawing on the international political economy theory of structural power, this article analyzes U.S. domestic and foreign economic policy and examines international governance outcomes from a historical perspective. It argues that U.S. replies to domestic and international political and economic constraints prompted significant structural changes to the international monetary and financial system. The paper concludes that it is American domestic decision-making that determines the structure of the international financial system due to American structural power to underwrite and rewrite the norms and rules of the international financial governance.     Recebido em: fevereiro/2018 Aprovado em: abril/2018